Chronic alcohol-induced brain states limit propagation of direct cortical stimulation - Habelt, Bettina; Talebi, Nasibeh; Afanasenkau, Dzmitry; Schwarz, Cindy; Knauer, Beate; Meinhardt, Marcus W.; Spanagel, Rainer; Werner, Carsten; Minev, Ivan R.; Beste, Christian; Bernhardt, Nadine (Scientific reports, 2025)
The impact of chronic alcohol consumption is evident in disruptions within prefrontal circuitries, resulting in cognitive deficits that underlie lost control over drinking. Given the limited efficacy of current pharmacotherapy, we employed multifunctional bioelectronics to investigate the potential of direct electrical brain stimulation to rectify neural impairments in alcohol-dependent rats. Cortical stimulation counteracted the observed deficiencies in event-related brain potentials and neural oscillations following chronic alcohol consumption, particularly by strengthening low-beta oscillations related to executive control. Stimulation efficacy thereby correlated with individual drinking patterns. In alcohol-dependent rats, stimulation-related neuroenhancement was spatially confined to the stimulation site, indicating reduced neural connectivity, as confirmed by a computational approach to directed functional connectivity patterns. Such state-dependent factors may contribute to the varying efficacy of brain stimulation observed in patients, ultimately suggesting the need for personalized neuromodulation designs.